The Greening of Google. - Upson, S.
Google's project is the largest corporate installation of solar panels in North America. It has grabbed headlines since Google announced it a year ago. That said, it isn't even in the worldwide top 10 of roof-mounted solar projects. A handful of factories in Germany and Japan take that honor, as well as a couple of roofs in Spain and the Netherlands. At the very least, the search giant's solar play adds one more country to the list of star performers in the world of commoditized sunshine. And it seems clear that Google's array won't be tops in North America for long.
Keywords: Building integrated photovoltaics; Corporate installation; Roof-mounted solar projects; Solar panels